PENGARUH BUDAYA ORGANISASI DAN KOMUNIKASI TERHADAP KINERJA APARATUR DESA KECAMATAN LENTENG: THE EFFECT OF ORGANIZATIONAL CULTURE AND COMMUNICATION ON THE PERFORMANCE OF VILLAGE APPARATUS, LENTENG DISTRICT - Khomaidi; Fatimah Riswati; Chamariyah (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2022)
This research was conducted in the village of Lenteng District, Sumenep Regency, with a total sample of 60 people. The objectives of this study were: 1) To determine and describe the influence of organizational culture, communication and competence on the performance of village officials, Lenteng District, Sumenep Regency; 2) To find out and test whether organizational culture, communication and competence partially have a significant influence on the performance of Village Apparatus, Lenteng District, Sumenep Regency; 3) To find out and test whether organizational culture, communication and competence simultaneously have a significant influence on the performance of the Village Apparatus, Lenteng District, Sumenep Regency. Data analysis using SPSS. This type of research is explanatory research using a quantitative research approach. The results showed that: 1) Partially, organizational culture, communication and competence have a significant influence on the performance of Village Apparatus, Lenteng District, Sumenep Regency. So that in this case the hypothesis is accepted and its validity is proven. This is evidenced by the t value of each independent variable of organizational culture (X1) of 3.567 with a significance level of 0.01, communication (X2) of 0.916 with a significance level of 0.03 and competence (X3) of 0.522 with a significance level. amounting to 0.04. All variables have a significant level less than 0.05 2). Simultaneously, organizational culture, communication and competence have a significant influence on the performance of Village Apparatus, Lenteng District, Sumenep Regency.